Electrometallurgical Principles - Shamsuddin M.; Sohn H.Y. (My University, 2025)
In this article, we discuss the principles involved in the electrolytic processing of different types of metal with an emphasis on the significant role of free energy and activity in electrowinning and electrorefining of common and reactive metals. Based on discharge potentials, metals are classified into three categories with respect to their characteristics of deposition from aqueous electrolytes without hydrogen evolution, under hydrogen overvoltage and only from fused electrolytes. © 2024 Elsevier Ltd. All rights reserved.